2012
DOI: 10.3109/14653249.2012.655420
|View full text |Cite
|
Sign up to set email alerts
|

Platelet lysate from whole blood-derived pooled platelet concentrates and apheresis-derived platelet concentrates for the isolation and expansion of human bone marrow mesenchymal stromal cells: production process, content and identification of active components

Abstract: Background aimsThe clinical use of human mesenchymal stromal cells (MSC) requires ex vivo expansion in media containing supplements such as fetal bovine serum or, alternatively, human platelet lysate (PL).MethodsPlatelet concentrates were frozen, quarantine stored, thawed and sterile filtered to obtain PL. PL content and its effect on fibroblast-colony-forming unit (CFU-F) formation, MSC proliferation and large-scale expansion were studied.ResultsPL contained high levels of basic fibroblast growth factor (bFGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
251
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(273 citation statements)
references
References 65 publications
15
251
1
2
Order By: Relevance
“…Moreover, it represents a good GMP-compliant alternative to animal serum for MSC clinical production confirming the recent data reported in the literature (18,36,37).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, it represents a good GMP-compliant alternative to animal serum for MSC clinical production confirming the recent data reported in the literature (18,36,37).…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, it is being established as a safe and efficient MSC culture supplement for robust MSC cultivation, thus offering certain advantages as potential FBS substitutes (18)(19)(20)(21). Analyses of platelet lysates, and subcellular fractions have shown that numerous bioactive molecules are stored within distinct platelet organelles including adhesive proteins, coagulation factors, mitogens, protease inhibitors, and proteoglycans (22).…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…For all experiments, MSC were cultured in clinical-grade a-modified Eagle's medium (a-MEM) (PAA) supplemented with 5% of clinical-grade human platelet lysate kindly provided by Markus T. Rojewski, 19 0.5% of ciprofloxacin (Bayer Pharma) and 1 U/mL of heparin (Sanofi-Aventis). Cells were cultured in a humidified atmosphere at 37°C and 5% CO 2 .…”
Section: Msc Culturementioning
confidence: 99%
“…28 Moreover, the medium and the process of MSC culture are critical as these parameters could influence MSC properties. 49 In this study, we used (1) human AM agreed for clinical use, (2) GMP culture medium supplemented with human platelet lysate produced in GMP condition and extensively studied by Fekete and colleagues 19 for ex vivo MSC expansion, (3) clinical-grade MSC from two different sources: BM 19 and AT. 21 Overall, our data showed that this construction is feasible and releases important cytokines and growth factors that are important in regulating wound healing and tissue regeneration.…”
mentioning
confidence: 99%
“…Further, the PDGF could regulate the wound healing and tissue regeneration by regulating the recruitment of fibroblasts and the precursor MSC and stimulating the generation of hydrogen peroxide which is required for cell migration 43, 44. It can be speculated that EGF and PDGF can be regarded as the safe mediums for MSC expansion and for clinical purposes 45, 46.…”
Section: Discussionmentioning
confidence: 99%